Influence of gender and oral health knowledge on DMFT index: a cross sectional study among school children in Kaski District, Nepal - Kamal Prasad Chapain; Krishna Gopal Rampal; Kalpana Gaulee Pokhrel; Chiranjivi Adhikari; Deependra Hamal; Khem Narayan Pokhrel (BMC Oral Health, 2023)
Abstract Background Oral health problems are highly prevalent among school children in Nepal. Poor oral health condition may be influenced by various factors. However, little is known about the sociodemographic and awareness related factors on oral health problems among school children in Nepal. Therefore, this study aimed to assess the association of gender and knowledge on DMFT index among school children. Methods A cross-sectional study was conducted among school children of Grade Seven in 12 schools of Kaski district in Nepal. Schools were randomly selected from the urban and semi-urban areas in the district. Data were collected covering oral health knowledge, socio-demographic characteristics, oral health condition and practices. The factors of poor oral health condition and practices were examined using t-test, one-way ANOVA, and multiple linear regression. Results Of the total participants (n = 669), 54.9% were females and their mean DMFT score was 1.82 (SD = 1.07). Total decayed score was higher among those who did not have knowledge that fluoride prevents decay compared to those who had knowledge about it (Being aware of fluoride prevents decay: Mean = 1.21 (SD = 1.54) versus not being aware of that: mean = 2.13 (SD = 2.13); p = 0.029). Females were more likely to have higher DMFT scores compared to males (β-coefficient = 0.43, 95% CI 0.13, 0.73, p = 0.005). In addition, higher knowledge score was negatively associated with higher DMFT score (β-coefficient = − 0.09, 95% CI − 0.20, -0.01, p = 0.047). Conclusion Being female students and those having lower level of knowledge on oral health attributed to higher DMFT index. Periodic dental check-up coupled with oral health education on regular brushing, use of fluoridated paste, tongue cleaning and care of gum diseases are recommended in schools.